The bone marrow in aplastic anaemia: Diagnostic and prognostic features. Issue 3 (March 1974) - Frisch, B.; Lewis, S. M.
Abstract : Bone marrow preparations were examined from 80 patients with aplastic anaemia. The degree of cellularity varied greatly and in a third of the cases it was normal or even hypercellular at one site of aspiration. In the severely hypoplastic marrows lymphoid cells were predominant and this situation was associated with a worse prognosis. There was no correlation between marrow lymphoid cell content and blood lymphocyte count but there was an inverse relationship between blood lymphocyte count and marrow erythroblasts and a close direct relationship between the blood neutrophil count and marrow myeloid cell content. In all cases a proportion of the erythroblasts showed morphological abnormalities. These included especially megaloblastic changes and asynchrony of nuclear-cytoplasmic maturation. There were also binucleated cells, internuclear chromatin bridges, intercellular cytoplasmic connexions, nuclear degenerative changes, namely, blurred outlines, irregular shapes, budding and fragmentation, and atypical mitotic figures. These appearances illustrate the extent to which a qualitative defect of erythropoiesis occurs as part of the haematological pattern in aplastic anaemia, and in some cases dominates the bone marrow picture. Similar cytological features were found in all cases, including five patients with Fanconi's anaemia.